Studying the snowball : validation of the typical buying center research method - Shashank Shekhar Aggarwal (2008)
This project aims to validate the "snowball" sampling technique, allied to a self-declared scale of decision influence, typically used for researching buying center behavior in a Business-to-Business environment. However this methodology suffers criticism such as biases in naming the people in the sample, and the limitations inherent in a self-declared scale of influence. These identified problems with the most-used method of investigating industrial buying center structures provide the focus of the research.